Explication of factors of the axiopsychological design of life achievements of modern youth - Inesa Antonivna Hulias; Ihor Mykolayovych Hoian (Insight: the psychological dimensions of society, 2022)
The article deals with an empirical study of the features of axiopsychological design of the life achievements of students – the future representatives of the “man-technique” profession (n=105). The importance of the issue under consideration was substantiated, and an empirical study was carried out. The concept of “axiopsychological design of an individual’s life fulfilment” was defined. It is noted that the understanding of the peculiarities of value design by the educators will allow the operationalization of addressing the tasks of educational and professional training of students in higher education institutions. The purpose of the article is to identify and reveal the predominant factors in the life fulfilment of senior students. Research methods: testing according to standardized questionnaires, quantitative analysis of the results of descriptive statistics, and factor analysis. Results. Factor analysis assisted in determining the structure of personal life fulfilment of modern youth. Ten factors, among which F1 “Masculine traits in achieving success” (10.38%) and F2 “Self-efficacy disposition” (9.62%) are key predictors of the process, were distinguished. The relationships between the components of each factor were specified. It was established the components of factors that have a negative load, which means their absence or low level of development, and hence “inhibit” the process of value design of young people, among them: “flexibility”, “self-regulation”, and “independence”. Conclusions. In order to eliminate “vulnerabilities” in the design of projects and the implementation of plans by senior students, we recommend paying attention to the aspects related to a better understanding of oneself, awareness of one’s problems, needs and motives, experiences, developing a positive attitude toward oneself and self-confidence, and forming adequate self-esteem, which will ultimately contribute to the processes of self-regulation and allow achieving goals under educational and professional tasks, and in the future – in all spheres of life.